1796 Incidence of and Risk Factors for Air Leaks in Preterm Infants Exposed to Restrictive use of Endotracheal Intubation. (October 2012) - Hummler, H; Parys, E; Essers, J; Hopfner, R; Beringer, O; Mayer, B; Fuchs, H; Schmid, M
Abstract : Introduction: The occurrence of air leaks such as pneumothorax (PTX), pneumopericardium (PPC) and pulmonary interstitial emphysema (PIE) may be a life-threatening condition in preterm infants. Aim of the Study: To study the incidence of and risk factors for air leaks in preterm infants treated with a policy of sustained inflations followed by non-invasive ventilation in the delivery room. Methods: Perinatal variables, variables of delivery room support and respiratory support in the NICU were analyzed retrospectively for infants with/without air leaks in preterm infants < 30 wks GA born 2005–2009 (n=297). Results: Median (range) gestational age was 26+0 (22+4–29+1) wks, birth weight was 790 (265–1660) g and 270/297 (91.0%) survived. 63 (21.2%) developed any air leak, 32 (10.8%) developed PTX, 44 (14.8%) PIE, and 1 (0.3%) PPC. Infants with air leaks had a higher risk for death (18 (28.6%) vs. 9 (3.8%), p<0.01) and for IVH Grade 3–4 (16 (25.4%) vs. 29 (12.4%), p<0.05). Air Leaks were associated with less use of prenatal steroids (44 (69.8%) vs. 199 (85.4%), p<0.01) and a more common use of cardiac compressions (9 (14.3%) vs. 11 (4.7%), p<0.01), use of a pressure of 30 cmH2 O for sustained inflations (32 (55.2)% vs. 80 (36.7%), p<0.05) and intubation during initial resuscitation (34 (54.0%) vs. 60 (25.6%), p<0.01). Conclusion: Air leaks were associated with an increased risk for mortality and severe IVH. Our approach resulted in a high rate of survival but was associated with a substantial rate of air leaks. Randomized trials are necessary further improve delivery room care.